Planning of Historical Centers: Case analysis with a Historical Urban Landscape approach - Pacheco Ponce, Diego Armando (2020)
A clear perception of the relationship between the Historical Centers and the city is vital to deter- mine the planning process. The management of the values and attributes of the Historic Center are a constant challenge that must be faced in the best way with citizen participation in the frame- work of strategic planning. The aim of this research is to analyze the planning of historical centers, through two Latin American experiences where the Historic Urban Landscape (HUL) approach has been applied. The cases correspond to the Historic Center of Lima-Peru and the Historic Center of Cuenca-Ecuador. Although this approach, promoted by Unesco since 2011, is controversial and de- batable among experts in the field, it is considered necessary and important to know how this new tool for the planning of historic centers is being implemented and the results it is generating.